DEVELOPMENT OF FILTERING POWER DIVIDER BASED ON SUBSTRATE INTEGRATED WAVEGUIDE BANDPASS FILTER AT 5.8 GHZ FREQUENCY - Budi Santiko, Arief
The future wireless communication system which leads to focus on Wireless Local Area Network (WLAN) is growing very fast. The development of WLAN devices including antennas, power dividers, and filters has raced to deliver the device to be compact-size, light-weight, and low-cost. In this research a power divider integrated with filtering process, named as filtering power divider (FPD), is developed for 5.8 GHz WLAN application. In order to have a compact size of the device, the proposed FPD is composed of bandpass filter (BPF) developed based on substrate integrated waveguide (SIW). The SIW-based BPF which is designed to operate at the frequency of 5.8 GHz also acts as an impedance matching circuit. The optimization is carried out using simulation software to investigate the effect of different filter parameters to the filtering process as well as to the output response of FPD. FPD is designed using a Duroid 5880 dielectric substrate with a thickness of 1.575 mm. FPD with power divide topology on a measurement result has a bandwidth response of 60 MHz in the frequency range of 5.915 GHz to 5.975 GHz and isolation between output ports is 20 dB and has the total dimensions of 95 mm x 70 mm. FPD with Wilkinson topology on a measurement result has a bandwidth response of 75 MHz in the frequency range of 5.9 GHz to 5.975 GHz and isolation between output ports with a 100? resistor of 30 dB and has the total dimensions of 95 mm x 80 mm.